Comparison of melting behaviors of edible oils using conventional and hyper differential scanning calorimetric scan rates - Mohammed, Abdulkarim Sabo; Mohd Ghazali, Hasanah (Universiti Putra Malaysia Press, 2007)
HyperDSC™ (fast scan rate) was used to study the melting behavior of canola (CLO), sunflower (SFO), palm olein (PO), rice bran oils (RBO), and cocoa butter (CB), and was compared to the melting behaviors using conventional DSC. There was an increase in sensitivity with increase in scan rate. Slow scan rate (5 to 20C/min) gave low sensitivity, which increased when the scan rates were increased to 50, 100 and 200C/min. Peak resolution was affected by scan rate depending on the sample weight. Increase in the size of sample coupled with the use of fast scan rate decreased the peak resolution. Generally small sample sizes gave better peak resolution. Results of the effect of scan rate on glass transition (Tg) shows that Tg, which is a weak transition especially in crystalline and low amorphous materials was not detected using conventional scan rates (5 to 20oC/min). It was however detected using of hyperDSC™ scan rates (100 to 200oC/min). Increasing the scan rate resulted in an increase in the peak temperature and the elimination of shoulder peaks, which were caused due to the polymorphic behavior of the triacylglycerols in the oils. The increase in peak temperature caused a shift in the peak position towards a higher temperature value. There is a positive correlation between the peak temperature and scan rate. The correlation coefficients (r) for CLO, SFO, PO, RBO and CB were 0.96, 0.95, 0.97, 0.96 and 0.96 respectively.